If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 6(x + -5) Reorder the terms: 24 = 6(-5 + x) 24 = (-5 * 6 + x * 6) 24 = (-30 + 6x) Solving 24 = -30 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 24 + -6x = -30 + 6x + -6x Combine like terms: 6x + -6x = 0 24 + -6x = -30 + 0 24 + -6x = -30 Add '-24' to each side of the equation. 24 + -24 + -6x = -30 + -24 Combine like terms: 24 + -24 = 0 0 + -6x = -30 + -24 -6x = -30 + -24 Combine like terms: -30 + -24 = -54 -6x = -54 Divide each side by '-6'. x = 9 Simplifying x = 9
| 3(2t-1)=9 | | 72=10+4m | | 6-2x=6x-10x+16 | | 5y+2=17 | | 7+2s-6=6s+3-3s | | 2x+45=5 | | 4y-2=33-3y | | 9-3w=2+4w | | 9y-3(y+4)=18 | | 7+4x-9=-6 | | 12x+8-5x=29 | | -5x+6=66 | | y=34x+3 | | y=x-6 | | 6=3x-1 | | 3+8y=40 | | 11t+1=1 | | 9x-7=-11 | | 5u-13=-10 | | 4y=-2x-8 | | y-x=8 | | x-y=5 | | 2x-3y=6 | | 200y-51=49 | | 50y-7=2 | | 6+3x=y | | 3+8x=0 | | x+4y=-8 | | 2x+(-2)y=12 | | 2x+y=5 | | 4x=y | | 5+y=x |